Conceptualising the relationship between shopper religiosity, perceived risk and the role of moral potency. Issue 5 (1st June 2016) - Baazeem, Thamer; Mortimer, Gary; Neale, Larry
Abstract: The primary aim of this paper is to conceptualise the influence of shopper religiosity on perceived risk and the moderating role of moral potency when purchasing religiously questionable products from retailers. An extensive review of extant literature was undertaken, drawing together the General Theory of Marketing Ethics and the concept of moral potency, in a retail context. A conceptual model is developed that provide the basis for future inquiry. The model elucidates the complex relationships between the dimensions of religiosity and social and psychological risk and then explains the moderating role of moral potency. The model offers a strong psychological explanation of how a shoppers' religion may increase their perceptions of risk in a purchase situation. The model also argues that risk perceptions may be heightened (or lessened) as a result of the shoppers' personal responsibility, confidence and courage. Retail managers may choose to implement this model in order to better predict shopper adoption behaviour of new religiously questionable products. The model allows for future empirical examinations across multiple shopping contexts and may be employed to estimate levels' demand for new products based on the extent of religiosity, moral potency and risk. The role of religion within retailing and shopping behaviour is emergent. Extant retailing literature has previously overlooked the role of religion as an antecedent to risk and the role of moral potency in moderating that relationship. This is the first paper to highlight these gaps and propose a testable model. Copyright © 2016 John Wiley & Sons, Ltd.